A graphene quantum dot/phthalocyanine conjugate: a synergistic catalyst for the oxygen reduction reaction. Issue 42 (16th May 2017) - Koh, Ki Hwan; Noh, Sung Hyun; Kim, Tae-Hyun; Lee, Won Jun; Yi, Sung-Chul; Han, Tae Hee
Abstract : In this work, a novel graphene quantum dot/iron phthalocyanine conjugate is synthesized. This hybrid material show efficient electrocatalytic activity via four electron reaction and distinguished tolerance toward methanol and CO. Abstract : Graphene quantum dots (GQDs) have gained great interest due to their chemical stabilities, unique catalytic activities, and feasible chemical functionalization opportunities; these have opened up new applications in the fields of chemical energy conversion and storage. Herein, we synthesized iron(ii ) phthalocyanine (FePC)–GQD conjugates as facile electrocatalysts for the enhanced oxygen reduction reaction (ORR), which is critical in energy conversion systems of fuel cells. This unique combination of materials (GQD–FePC) exhibits a greatly enhanced onset potential via a four-electron pathway in an alkaline electrolyte. Moreover, the synthesized electrocatalyst shows distinguished tolerance toward methanol and carbon monoxide, which paves the way for its commercialization as an electrocatalyst.